AKTUALISASI GURITAN DALAM KARAWITAN GAGRAG BANYUMAS - Darno Darno (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2008)
The essence of guritan is a poetry, it is a kind of belles-lettres that aesthetic’s consideration with engaging more strongly in word’s selection, language’s style, rhyme, and poetric meter. In a traditionally manner, Banyumas’ society have known the poetry’s musicality, by getting san a guritan in musical arrangement called gendhing. The existence of guritan in a karawitan gagrag Banyumas have experienced more than belles-lettres. In which it has a aesthetic expression’s process engaging musical media. Else in which engaged to the cultural background, individual’s experience, and emotional contact’s intensity between individual whose became a part of musical’s garap process. Keywords : actualization, guritan, karawitan gagrag Banyumas